MENINGKATKAN KREATIVITAS JIWA ENTERPRENUER DI ERA NEW NORMAL PADA REMAJA MASJID - Riyadini Riyan Utami; Sri Karnila; Muhammad Saputra; Yuniwati Yuniwati (LPPM Universitas Bina Bangsa, 2022)
This service is carried out on the youth of the mosque, in using used clothes to make bag arrangements. The mosque is a place or means of worship for Muslims, the function of the mosque is not only used as a place of worship but can be a center of activity for Muslims in the community such as mosque youth. The youth of the Marhdotillah Rajabasa mosque is one of the youth organizations of the mosque in the Glora Persada Rajabasa Raya housing area. Some of the routine activities carried out by the youth of this mosque include regular recitations, mosque service work, helping prepare for major Islamic holidays, and helping teach the Koran to children in the neighborhood. The general activities carried out by the youth of this mosque require creativity and an entrepreneurial spirit in accordance with the function of the mosque as a place of worship but also as a development of community life activities. For this reason, this service activity seeks to provide additional creativity by utilizing used goods such as used clothes that are used as tote bags. Creativity is creating new things or making something new, creativity is very important to be owned by a person, or group of people. Totebag is a product that is expected to increase the creativity of mosque youth by providing socialization of creativity material to open creative thinking patterns in mosque youth. Then provide material for making arrangements and practice in manufacturing. The result of this service is a product that has economic value and is environmentally friendly